Identification of lipid synthesis and secretion proteins in bovine milk. Issue 1 (16th January 2014) - Lu, Jing; van Hooijdonk, Toon; Boeren, Sjef; Vervoort, Jacques; Hettinga, Kasper
<x content-type="archive" xml:space="preserve">Abstract</x> Lactation physiology is a process that is only partly understood. Proteomics techniques have shown to be useful to help advance the knowledge on lactation physiology in human and rodent species but have not been used as major tools for dairy cows, except for mastitis. In this paper, advanced non-targeted proteomics techniques (Filter aided sample preparation and NanoLC-Orbitrap-MS/MS) were applied to study the milk fat globule membrane and milk serum fraction, resulting in the identification of 246 proteins. Of these, 23 transporters and enzymes were related to lipid synthesis and secretion in mammary gland and their functions are discussed in detail. The identification of these intracellular transporters and enzymes in milk provides a possibility of using milk itself to study lipid synthesis and secretion pathways. This full-scale scan of milk proteins by using non-targeted proteomic analysis helps to reveal the important proteins involved in lipid synthesis and secretion for further examination in targeted studies.